INTEGRASI ISU SOSIOSAINTIFIK DALAM PEMBELAJARAN IPAS UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Aulia Deswita Zahra; Baharudin Baharudin; Deri Firmansah (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
ABSTRACT Science and Social Studies (IPAS) learning in elementary schools is expected not only to facilitate conceptual understanding but also to foster students’ ability to evaluate information, construct logical arguments, and make reasoned decisions. In practice, however, critical thinking skills often remain underdeveloped because classroom activities tend to be teacher-centered, limiting students’ opportunities to engage with authentic problems and analytical discussions. This condition prompted the integration of socioscientific issues into IPAS instruction as a means of connecting scientific concepts with real-world situations relevant to students’ daily lives. The study involved 23 fifth-grade students selected through purposive sampling. Changes in students’ critical thinking skills were examined using an essay-based assessment developed according to Ennis’s critical thinking indicators. A quantitative approach employing a one-group pretest–posttest design was used to compare students’ performance before and after the learning intervention. The collected data were analyzed through descriptive statistics, paired-sample t-test, and N-Gain analysis. The findings revealed a noticeable improvement in students’ critical thinking skills following the implementation of socioscientific issue-based learning. Statistical testing indicated a significant difference between pretest and posttest scores, with a significance value of 0.001. The average N-Gain score reached 0.4720, which falls within the moderate improvement category. Beyond enhancing critical thinking, the learning approach also encouraged students to develop a more contextual, active, and reflective understanding of IPAS concepts. These results suggest that integrating socioscientific issues into elementary school instruction offers a promising alternative for supporting the development of students’ critical thinking abilities. ABSTRAK Pembelajaran IPAS di sekolah dasar tidak hanya ditujukan untuk menguasai konsep, tetapi juga untuk melatih peserta didik menilai informasi, mengemukakan alasan, dan mengambil keputusan secara rasional. Kenyataannya, keterampilan berpikir kritis masih belum berkembang secara optimal karena aktivitas belajar lebih banyak didominasi oleh guru sehingga kesempatan siswa untuk menganalisis permasalahan nyata menjadi terbatas. Situasi tersebut mendorong penerapan isu sosiosaintifik sebagai konteks pembelajaran yang menghubungkan materi IPAS dengan persoalan yang dekat dengan kehidupan peserta didik. Penelitian ini melibatkan 23 siswa kelas V yang dipilih melalui purposive sampling. Perubahan kemampuan berpikir kritis diamati melalui tes esai yang disusun berdasarkan indikator Ennis. Data yang diperoleh dibandingkan antara kondisi sebelum dan sesudah pembelajaran dengan pendekatan kuantitatif menggunakan desain one-group pretest-posttest. Analisis dilakukan melalui statistik deskriptif, paired sample t-test, dan perhitungan N-Gain. Hasil pengukuran menunjukkan adanya peningkatan kemampuan berpikir kritis setelah siswa mengikuti pembelajaran berbasis isu sosiosaintifik. Perbedaan skor sebelum dan sesudah perlakuan terbukti signifikan dengan nilai signifikansi 0,001. Tingkat peningkatan yang diperoleh berada pada kategori sedang dengan rata-rata N-Gain sebesar 0,4720. Selain memperkuat kemampuan berpikir kritis, pembelajaran ini juga mendorong siswa memahami konsep IPAS secara lebih kontekstual, aktif, dan reflektif. Temuan tersebut menunjukkan bahwa integrasi isu sosiosaintifik layak dipertimbangkan sebagai alternatif strategi pembelajaran untuk mendukung pengembangan keterampilan berpikir kritis di sekolah dasar.